Training of Specialists for Working with Special Children at the Kyiv Institute of People's Education (1920–1930) - Ляпіна, О. (Київський національний університет імені Тараса Шевченка, 2020)
This paper is devoted to the history of special pedagogy formation at the Kyiv Institute of People's Education. It reconstructs the initial stage of this process, namely the establishment of the medical and pedagogical faculty in 1920, and determines the features of its functioning, staffing, and reasons for structural transformations during 1921–1924. It proves that educational programs for the training of Ukrainian special education teachers were created and successfully implemented in a fairly short period of time, as well as that the interaction with city specialized children's institutions where students could undergo not only passive but also active practical training, was established. It focuses on the fact that leading Ukrainian specialists in defectology were involved in teaching at the institute during that period, thus students not only were acquainted with the latest achievements of correctional pedagogy but also had an opportunity to acquire applied skills under the guidance of practicing doctors. The paper also highlights the key reasons for the closure of training of special education teachers at the Institute in 1924. It founds that the change in the attitude of the state towards children with physical and mental disabilities in the late 1920s led to the reopening of the defectology department at the Kyiv Institute of Public Education (in 1929). It defines the main problems of its short-term history, as well as generalizes and specifies information about the actual head of the department O. M. Shcherbyna. It is thanks to the latter that the branch training of specialists under the categories of psychophysical deviations of children was taking place in the Kyiv IPE. The paper studies the main trends, positive achievements, and shortcomings of the formation of the Ukrainian system of training of special education teachers at the Kyiv IPE (1920–1930), which was the only higher educational institution in Ukraine training pedagogical personnel for the needs of a special school.

Присвячено історії становлення спеціальної педагогіки в Київському інституті народної освіти. Реконструйовано початковий етап цього процесу – створення лікарсько-педагогічного факультету в 1920 р., визначено особливості його функціонування, кадрового забезпечення, причини структурних трансформацій протягом 1921–1924 рр., виокремлено ключові причини згортання підготовки дефектологів в інституті в 1924 р. Окрему увагу приділено повторному директивному відкриттю дефектологічного відділу в Київському ІНО (1929), охарактеризовано головні проблеми його короткотривалої історії. Розглянуто основні тенденції, позитивні здобутки і недоліки формування української системи підготовки фахівців-дефектологів в Київському ІНО (1920–1930).
Підготовка спеціалістів для роботи з особливими дітьми в Київському інституті народної освіти (1920–1930)
Keywords: лікарсько-педагогічний факультет; дефектологічий відділ; Київський інститут народної освіти; корекційна освіта; спеціальна освіта; medical and pedagogical faculty; defectology department; Kyiv Institute of People's Education; special education; correctional education